Creating a responsible authorship culture in science: Anchoring authorship practices in principles of transparency, credit, and accountability - Véronique Kiermer; Sofia Adams; Kirsten Bibbins-Domingo; Yensi Flores Bueso; Kathleen Hall Jamieson; Joerg Heber; Mohammad Hosseini; Ana Marušić; Beau Nielsen; Magdalena Skipper; Geeta K. Swamy; Susan M. Wolf (Proceedings of the National Academy of Sciences, 2026)
Authorship remains the primary currency of academic credit and a cornerstone of research integrity, yet current practices often fail to reflect the collaborative and interdisciplinary nature of modern science and questionable authorship practices persist. We argue that addressing these shortcomings is a collective responsibility shared by researchers, journals, research funders, scholarly societies, and research institutions. We examined authorship guidelines issued by journals and research institutions and found that their recommendations to researchers are highly variable. We propose that fostering a responsible authorship culture requires a shared, principle-based framework grounded in transparency, credit, and accountability. These three interconnected principles highlight when authorship practices are questionable and offer a framework for constructive reflection on the meaning of authorship. We outline practical ways research leaders can embed these principles into everyday practice by initiating early, inclusive, and fair authorship discussions and ensuring transparent description of contributions. Research institutions have a unique opportunity to inculcate good practices and lead this culture change with harmonized guidance, education, fair conflict resolution, and reform of researcher assessment. Anchoring authorship in transparency, credit, and accountability will strengthen the credibility of individual research, the fairness of recognition systems, and, ultimately, the trustworthiness of science itself.